Photocatalyst, preparation method, use and treatment method of polyvinyl alcohol

Through the calcination preparation method of titanate, water-soluble inorganic lanthanum salt and polyvinyl alcohol, a lanthanum-doped titanium dioxide photocatalyst was prepared, which solved the problem of poor degradation performance of existing photocatalysts on polyvinyl alcohol and achieved efficient polyethylene Vinyl alcohol degradation effect.

CN116712989BActive Publication Date: 2024-12-24GUANGZHOU XINHUA TECHNICAL SERVICE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310656673.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-05
Publication Date
2024-12-24
Estimated Expiration
2043-06-05

AI Technical Summary

Technical Problem

The existing photocatalysts have poor degradation performance on polyvinyl alcohol and are difficult to degrade efficiently.

Method used

Using titanate, water-soluble inorganic lanthanum salt and polyvinyl alcohol as raw materials, lanthanum doped titanium dioxide photocatalyst is prepared by calcination, and combined with appropriate solvents and conditions, the degradation efficiency of the photocatalyst is improved.

Benefits of technology

The degradation rate of polyvinyl alcohol by photocatalysts is significantly improved, and efficient degradation within 80 to 200 minutes can be achieved, with a degradation rate of up to 93.18%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116712989B_ABST
    Figure CN116712989B_ABST
Patent Text Reader

Abstract

The present invention discloses a photocatalyst, a preparation method, a use and a method for treating polyvinyl alcohol. The preparation method of the present invention comprises the following steps: (1) adding a second liquid to a first liquid under stirring to obtain a photocatalyst precursor; wherein the first liquid comprises a titanate and a first solvent; the first solvent comprises a monohydric alcohol and a carboxylic acid; wherein the second liquid comprises a water-soluble inorganic lanthanum salt, polyvinyl alcohol and a second solvent; the second solvent comprises water and a monohydric alcohol; the molar volume ratio of the water-soluble inorganic lanthanum salt to the titanate is (0.0015-0.004):10 mol / L, and the mass volume ratio of the polyvinyl alcohol to the titanate is (0.1-0.2):10 g / L; (2) calcining the photocatalyst precursor at 350-450°C to obtain a photocatalyst. The preparation method can improve the degradation rate of polyvinyl alcohol by the photocatalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a photocatalyst and a preparation method and application thereof, and a method for treating polyvinyl alcohol. Background Art

[0002] Polyvinyl alcohol slurry is widely used in the fields of industry, construction, medicine, textile, agriculture, etc. Polyvinyl alcohol can be used to prepare polyvinyl acetal, gasoline-resistant pipes and vinylon synthetic fibers, and can also be used as a fabric treatment agent, emulsifier, paper coating, adhesive, etc. However, polyvinyl alcohol is difficult to degrade, and how to efficiently degrade polyvinyl alcohol is an urgent problem to be solved.

[0003] CN100377778C discloses a method for synthesizing a titanium oxide photocatalyst excited by visible light. Dissolve thiourea, lanthanum nitrate or lanthanum chloride, polyethylene glycol or polyvinyl alcohol in distilled water and mix them evenly; prepare a 1-5 mol / L TiCl4 aqueous solution; mix the above solutions evenly and prepare a final solution, so that the molar ratio of thiourea to titanium tetrachloride is 1:0.2-2, the content of lanthanum nitrate or lanthanum chloride is 0.01-1.5 mol%, and the content of polyethylene glycol or polyvinyl alcohol is 0.5-3 mol%; place the final solution in an autoclave for hydrothermal treatment at 150-250°C for 0.5-5 hours to obtain a precipitate; wash the precipitate with distilled water to remove chloride ions, and then wash it with alcohol and dry it. The photocatalyst has poor degradation performance for polyvinyl alcohol.

[0004] CN109331808A discloses a microwave synthesis method of a lanthanum / titanium dioxide nanocomposite photocatalyst. A surfactant is dissolved in water, phthalein sulfate and lanthanum nitrate are added, and the mixture is dispersed evenly to obtain a mixed solution A; urea is added to the mixed solution A, and the mixture is dispersed evenly to obtain a mixed solution B; the mixed solution B is heated under microwaves for reaction, and after the reaction is complete, it is cooled to obtain a mixed solution C; the upper clear liquid of the mixed solution C is discarded, the lower liquid is retained, and then centrifugation is performed to wash and obtain a precipitate, and the precipitate is dried; and heat treatment is performed to obtain a composite photocatalyst. The catalyst has poor degradation performance for polyvinyl alcohol. Summary of the invention

[0005] In view of this, one object of the present invention is to provide a method for preparing a photocatalyst, which can improve the degradation rate of polyvinyl alcohol by the photocatalyst. Another object of the present invention is to provide a photocatalyst. Another object of the present invention is to provide a use of a photocatalyst. Another object of the present invention is to provide a method for treating polyvinyl alcohol, which can improve the degradation rate of polyvinyl alcohol.

[0006] The above purpose is achieved through the following technical solutions.

[0007] In one aspect, the present invention provides a method for preparing a photocatalyst, comprising the following steps:

[0008] (1) adding a second liquid to the stirred first liquid to obtain a photocatalyst precursor;

[0009] Wherein, the first liquid includes titanate and a first solvent; the first solvent includes a monohydric alcohol containing 1 to 6 carbon atoms and a carboxylic acid containing 1 to 6 carbon atoms;

[0010] The second liquid includes a water-soluble inorganic lanthanum salt, polyvinyl alcohol and a second solvent; the second solvent includes water and a monohydric alcohol containing 1 to 6 carbon atoms;

[0011] The molar volume ratio of the water-soluble inorganic lanthanum salt to the titanate is (0.0015-0.004):10 mol / L, and the mass volume ratio of the polyvinyl alcohol to the titanate is (0.1-0.2):10 g / L;

[0012] (2) The photocatalyst precursor is calcined at 350-450° C. to obtain a photocatalyst.

[0013] According to the preparation method of the present invention, preferably, the titanate has a structure shown in formula (I):

[0014]

[0015] Wherein, R1, R2, R3 and R4 are independently selected from C1 to C8 alkyl groups;

[0016] The water-soluble inorganic lanthanum salt is selected from one or more of lanthanum nitrate and lanthanum chloride.

[0017] According to the preparation method of the present invention, preferably, in the first solvent, the volume ratio of the monohydric alcohol to the carboxylic acid is (3-8):2; in the second solvent, the volume ratio of water to the monohydric alcohol is 10.29:(5.5-8.5).

[0018] According to the preparation method of the present invention, preferably, in the first liquid, the volume ratio of the titanate to the first solvent is 10:(30-60); in the second liquid, the content of the water-soluble inorganic lanthanum salt is 0.07-0.17 mmol / L, and the content of the polyvinyl alcohol is 5-15 mg / L.

[0019] According to the preparation method of the present invention, preferably, the speed at which the second liquid is added to the first liquid is 10 to 25 mL / h.

[0020] According to the preparation method of the present invention, preferably, the carboxylic acid in the first solvent is selected from one or more of formic acid, acetic acid, propionic acid, isopropionic acid, butyric acid, and isobutyric acid; the monohydric alcohol in the first solvent is selected from one or more of methanol, ethanol, propanol, isopropanol, butanol, and isobutanol; and the monohydric alcohol in the second solvent is selected from one or more of methanol, ethanol, propanol, isopropanol, butanol, and isobutanol.

[0021] According to the preparation method of the present invention, preferably, the calcination time is 0.5 to 4 hours.

[0022] In another aspect, the present invention provides a photocatalyst prepared by the above method.

[0023] In still another aspect, the present invention provides use of the above-mentioned photocatalyst in degrading polyvinyl alcohol.

[0024] In another aspect, the present invention provides a method for treating polyvinyl alcohol using the above-mentioned photocatalyst, comprising the following steps:

[0025] The photocatalyst is placed in a polyvinyl alcohol solution and catalytically decomposed for 80 to 200 minutes under light conditions; wherein, for every 0.015 g of polyvinyl alcohol, the amount of the photocatalyst is 35 to 65 mg.

[0026] The present invention uses polyvinyl alcohol as a template and prepares a lanthanum-doped titanium dioxide photocatalyst in combination with appropriate parameters and conditions. The photocatalyst of the present invention has a good degradation effect on polyvinyl alcohol. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a scanning electron microscope image of the photocatalyst obtained in Example 1 magnified 75,000 times.

[0028] Figure 2 This is a scanning electron microscope image of the photocatalyst obtained in Example 1 magnified 100,000 times.

[0029] Figure 3 This is the infrared spectrum of the photocatalyst precursor of Example 1.

[0030] Figure 4 This is the infrared spectrum of the photocatalyst obtained in Example 1.

[0031] Figure 5 This is the XRD spectrum of the photocatalyst obtained in Example 1. DETAILED DESCRIPTION

[0032] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0033] <Photocatalyst preparation method>

[0034] The method for preparing the photocatalyst of the present invention comprises the following steps: (1) preparing a photocatalyst precursor; and (2) obtaining the photocatalyst.

[0035] Steps for preparing photocatalyst precursors

[0036] The second liquid is added to the first liquid being stirred to obtain a photocatalyst precursor. The first liquid can be stirred with a magnetic stirrer.

[0037] The first liquid of the present invention comprises a carbonate and a first solvent. In certain embodiments, the first liquid consists of a carbonate and a first solvent.

[0038] Titanate has the structure shown in formula (I):

[0039]

[0040] In formula (I), R1, R2, R3 and R4 are independently selected from C1 to C8 alkyl groups; preferably, R1, R2, R3 and R4 are independently selected from C2 to C6 alkyl groups; more preferably, R1, R2, R3 and R4 are independently selected from C3 to C5 alkyl groups. Examples of alkyl groups include, but are not limited to, methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, 1-methylbutyl, 2-methylbutyl, 3-methylbutyl, 1-ethylpropyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, 2,2-dimethylpropyl. According to one embodiment of the present invention, the titanate is butyl titanate. This is conducive to reaction with the polyvinyl alcohol template.

[0041] The volume ratio of the carbonate ester to the first solvent is 10:(30-60); preferably 10:(40-50); more preferably 10:(40-45).

[0042] The first solvent includes a monohydric alcohol containing 1 to 6 carbon atoms and a carboxylic acid containing 1 to 6 carbon atoms. In certain embodiments, the first solvent consists of a monohydric alcohol containing 1 to 6 carbon atoms and a carboxylic acid containing 1 to 6 carbon atoms.

[0043] The monohydric alcohol is preferably an aliphatic monohydric alcohol. The number of carbon atoms contained in the monohydric alcohol is 1 to 6, preferably 2 to 5, and more preferably 2 to 3. Examples of the monohydric alcohol include, but are not limited to, one or more of methanol, ethanol, propanol, isopropanol, butanol, and isobutanol.

[0044] The carboxylic acid is preferably an aliphatic carboxylic acid. The carboxylic acid is a monocarboxylic acid. The number of carbon atoms contained in the carboxylic acid is 1 to 6, preferably 2 to 5, and more preferably 2 to 3. Examples of the carboxylic acid include, but are not limited to, formic acid, acetic acid, propionic acid, isopropionic acid, butyric acid, and isobutyric acid.

[0045] In the first solvent, the volume ratio of the monohydric alcohol to the carboxylic acid is (3-8):2; preferably (4-7):2; more preferably (5-6):2.

[0046] In some embodiments, the method further comprises the step of preparing a first liquid: uniformly mixing a monohydric alcohol and a carboxylic acid to form a first solvent, dropping a titanate into the first solvent and stirring to obtain a first liquid. Magnetic stirring may be used.

[0047] The second liquid of the present invention comprises a water-soluble inorganic lanthanum salt, polyvinyl alcohol and a second solvent. In certain embodiments, the second liquid consists of a water-soluble inorganic lanthanum salt, polyvinyl alcohol and a second solvent.

[0048] The water-soluble inorganic lanthanum salt can be selected from one or more of lanthanum chloride or lanthanum nitrate. Preferably, the water-soluble inorganic lanthanum salt is lanthanum nitrate. In the second liquid, the concentration of the water-soluble inorganic lanthanum salt can be 0.07 to 0.17 mmol / L; preferably 0.01 to 0.15 mmol / L; more preferably 0.011 to 0.13 mmol / L.

[0049] The concentration of polyvinyl alcohol in the second liquid may be 5 to 15 mg / L, preferably 7 to 10 mg / L, and more preferably 8 to 9 mg / L.

[0050] The second solvent includes water and a monohydric alcohol containing 1 to 6 carbon atoms. In certain embodiments, the second solvent consists of water and a monohydric alcohol containing 1 to 6 carbon atoms.

[0051] The monohydric alcohol is preferably an aliphatic monohydric alcohol. The number of carbon atoms contained in the monohydric alcohol is 1 to 6, preferably 2 to 5, and more preferably 2 to 3. Examples of the monohydric alcohol include, but are not limited to, one or more of methanol, ethanol, propanol, isopropanol, butanol, and isobutanol.

[0052] The volume ratio of water to monohydric alcohol in the second solvent may be 10.29:(5.5-8.5); preferably 10.29:(6-8); more preferably 10.29:(6.5-7.5).

[0053] The speed at which the second liquid is added to the first liquid may be 10 to 25 mL / h, preferably 15 to 20 mL / h, and more preferably 16 to 18 mL / h.

[0054] In some embodiments, the step of preparing a second liquid is further included: adding a second solvent and a polyvinyl alcohol solution to the water-soluble inorganic lanthanum salt solution. The concentration of the water-soluble inorganic lanthanum salt solution can be 0.05-0.3 mol / L; preferably 0.08-0.15 mol / L. The concentration of the polyvinyl alcohol solution can be 0.1-1.0 g / L; preferably 0.3-0.7 g / L. The volume ratio of the water-soluble inorganic lanthanum salt solution, water, monohydric alcohol and polyvinyl alcohol solution can be (0.01-0.04):10:(5-9):(0.1-0.5); preferably (0.02-0.03):10:(6-8):(0.3-0.4).

[0055] The molar volume ratio of the water-soluble inorganic lanthanum salt to the titanate is (0.0015-0.004):10 mol / L, preferably (0.002-0.003):10 mol / L, and more preferably (0.002-0.025):10 mol / L. This can increase the degradation rate of polyvinyl alcohol by the photocatalyst.

[0056] The mass volume ratio of polyvinyl alcohol to titanate is (0.1-0.2):10 g / L, preferably (0.12-0.18):10 g / L, and more preferably (0.15-0.17):10 g / L. This can increase the degradation rate of polyvinyl alcohol by the photocatalyst.

[0057] Steps to obtain photocatalyst

[0058] The photocatalyst precursor is calcined to obtain a photocatalyst.

[0059] The calcination temperature is 350-450° C., preferably 380-420° C., and more preferably 400-410° C. The present invention finds that the calcination temperature has an important influence on the degradation rate of polyvinyl alcohol by the photocatalyst, and a calcination temperature that is too high or too low is not conducive to improving the degradation rate of polyvinyl alcohol.

[0060] The calcination time may be 0.5 to 4 hours, preferably 1 to 3 hours, and more preferably 2 to 2.5 hours.

[0061] <Photocatalyst and its use>

[0062] The photocatalyst of the present invention is prepared by the above method. The titanium dioxide in the photocatalyst is anatase-type. The photocatalyst of the present invention has a good degradation effect on polyvinyl alcohol, and therefore, the present invention provides the use of the photocatalyst in the degradation of polyvinyl alcohol.

[0063] <Photocatalytic Degradation Method of Polyvinyl Alcohol>

[0064] The photocatalyst is placed in a polyvinyl alcohol solution and catalytically decomposed under the irradiation of a light source to obtain a polyvinyl alcohol solution after photocatalysis. The photocatalyst is specifically as described above and will not be repeated here. The light source can be a xenon lamp.

[0065] The polyvinyl alcohol solution is composed of polyvinyl alcohol and water. The concentration of polyvinyl alcohol can be (0.05-0.5) g / L, preferably (0.08-0.3) g / L, and more preferably (0.1-0.15) g / L.

[0066] For every 0.015g of polyvinyl alcohol, the amount of photocatalyst used is 35-65mg, preferably 40-60mg, and more preferably 45-50mg. The present invention finds that too much or too little amount of photocatalyst is not conducive to improving the degradation rate of polyvinyl alcohol.

[0067] The catalytic decomposition time is 80 to 200 minutes, preferably 100 to 180 minutes, and more preferably 150 to 170 minutes, which helps to increase the degradation rate of polyethylene and improve efficiency.

[0068] Here is the test method:

[0069] Degradation rate of polyvinyl alcohol:

[0070] The polyvinyl alcohol solution and the polyvinyl alcohol solution after photocatalysis were tested with a spectrophotometer, and then the degradation rate of polyvinyl alcohol was calculated from the absorbance value according to the following formula:

[0071] (A0-A) / A0

[0072] A0 represents the absorbance of the polyvinyl alcohol solution; A represents the absorbance of the polyvinyl alcohol solution after photocatalysis.

[0073] Example 1

[0074] (1) 30 mL of anhydrous ethanol and 12 mL of glacial acetic acid were mixed evenly, and then 10 mL of butyl titanate was slowly dropped into the mixture with magnetic stirring to obtain a first liquid.

[0075] To 0.02 mL of a 0.1 mol / L lanthanum nitrate solution, 10 mL of distilled water, 7 mL of anhydrous ethanol, and 0.3 mL of a 0.5 g / L polyvinyl alcohol solution were added to obtain a second liquid.

[0076] The second liquid is added to the first liquid under magnetic stirring to obtain a photocatalyst precursor. The time taken for the second liquid to be added to the first liquid is 1 hour.

[0077] (2) The photocatalyst precursor was calcined at 400°C for 2 hours to obtain a photocatalyst.

[0078] Figure 3Medium 3433cm -1 The strong absorption peak at 1120cm is the characteristic peak of -OH stretching vibration in polyvinyl alcohol and titanium dioxide. -1 The absorption peak at is the stretching vibration absorption peak of the secondary alcohol hydroxyl group CO of polyvinyl alcohol. It can be seen that the present invention successfully synthesizes the molecular imprinting photocatalyst using polyvinyl alcohol as a template.

[0079] Depend on Figure 5 It can be seen that the titanium dioxide in the photocatalyst of the present invention is anatase type.

[0080] Comparative Examples 1-2

[0081] Except that the amount of lanthanum nitrate solution used is 0.01 mL (Comparative Example 1) and 0.05 mL (Comparative Example 2), the rest is the same as Example 1.

[0082] Comparative Examples 3-4

[0083] Except that the amounts of the polyvinyl alcohol solution used were 0.1 mL (Comparative Example 3) and 0.5 mL (Comparative Example 4), the rest were the same as in Example 1.

[0084] Comparative Examples 5-6

[0085] Except that the calcination temperature is 300° C. (Comparative Example 5) and 500° C. (Comparative Example 6), the rest is the same as Example 1.

[0086] Example 2

[0087] 45 mg of the photocatalyst prepared in Example 1 was placed in 150 mL of a polyvinyl alcohol solution with a concentration of 0.1 g / L, and catalytically decomposed for 150 min under the irradiation of a xenon lamp to obtain a photocatalyzed polyvinyl alcohol solution.

[0088] The degradation rate of polyvinyl alcohol was 93.18%.

[0089] Example 3

[0090] Except that the amount of the photocatalyst was 60 mg, the rest was the same as in Example 2. The degradation rate of polyvinyl alcohol was 90.87%.

[0091] Examples 4 and 5

[0092] Except that the catalytic decomposition time is 105 min (Example 4) and 180 min (Example 5), the rest is the same as Example 2. The degradation rate of polyvinyl alcohol is shown in Table 1.

[0093] Table 1

[0094] Serial number Degradation rate (%) Example 4 72.21 Example 5 93.02

[0095] Comparative Examples 7 to 13

[0096] Except that the amount of the photocatalyst is 25 mg and the selection of the photocatalyst is as shown in Table 2, the rest is the same as Example 2. The degradation rate of polyvinyl alcohol is shown in Table 2.

[0097] Table 2

[0098]

[0099] Comparative Example 14

[0100] Except that the photocatalyst is nano titanium dioxide, the rest is the same as Example 2. Nano titanium dioxide is purchased from Tianjin Chemical Reagent Supply and Marketing Company and has analytical purity. The degradation rate of polyvinyl alcohol is 12.57%.

[0101] Comparative Example 15

[0102] Except that the photocatalyst is different from that in Example 2, the rest is the same as in Example 2. The photocatalyst is prepared by the following method:

[0103] Mix 30 mL of anhydrous ethanol and 12 mL of glacial acetic acid, then slowly drop 10 mL of butyl titanate and stir magnetically to obtain solution A. Take 0.02 mL of lanthanum nitrate (0.1 mol / L) solution, add 10 mL of distilled water and 7 mL of anhydrous ethanol to obtain solution B. Add solution B to solution A under magnetic stirring within 1 hour.

[0104] The degradation rate of polyvinyl alcohol was 58.53%.

[0105] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.

Claims

1. Use of a photocatalyst in degrading polyvinyl alcohol, characterized in that: The photocatalyst is prepared by the following method: (1) adding the second liquid to the stirred first liquid to obtain a photocatalyst precursor; Wherein, the first liquid includes titanate and a first solvent; the first solvent includes a monohydric alcohol containing 1 to 6 carbon atoms and a carboxylic acid containing 1 to 6 carbon atoms; The second liquid includes a water-soluble inorganic lanthanum salt, polyvinyl alcohol and a second solvent; the second solvent includes water and a monohydric alcohol containing 1 to 6 carbon atoms; The molar volume ratio of the water-soluble inorganic lanthanum salt to the titanate is (0.0015-0.004):10 mol / L, and the mass volume ratio of the polyvinyl alcohol to the titanate is (0.1-0.2):10 g / L; (2) The photocatalyst precursor is calcined at 350-450° C. to obtain a photocatalyst.

2. The use according to claim 1, characterized in that The titanate has a structure shown in formula (I): Wherein, R1, R2, R3 and R4 are independently selected from C1 to C8 alkyl groups; The water-soluble inorganic lanthanum salt is selected from one or more of lanthanum nitrate and lanthanum chloride.

3. The use according to claim 1, characterized in that In the first solvent, the volume ratio of the monohydric alcohol to the carboxylic acid is (3-8):2; in the second solvent, the volume ratio of water to the monohydric alcohol is 10.29:(5.5-8.5).

4. The use according to claim 1, characterized in that In the first liquid, the volume ratio of titanate to the first solvent is 10:(30-60); in the second liquid, the content of water-soluble inorganic lanthanum salt is 0.07-0.17 mmol / L, and the content of polyvinyl alcohol is 5-15 mg / L.

5. The use according to claim 1, characterized in that: The speed at which the second liquid is added to the first liquid is 10-25 mL / h.

6. The use according to claim 1, characterized in that: The carboxylic acid in the first solvent is selected from one or more of formic acid, acetic acid, propionic acid, and butyric acid; the monohydric alcohol in the first solvent is selected from one or more of methanol, ethanol, propanol, and butanol; and the monohydric alcohol in the second solvent is selected from one or more of methanol, ethanol, propanol, and butanol.

7. The use according to any one of claims 1 to 6, characterized in that: The calcination time is 0.5 to 4 hours.

8. A method for treating polyvinyl alcohol using a photocatalyst, characterized in that: The steps include: The photocatalyst is placed in a polyvinyl alcohol solution and catalytically decomposed under light conditions for 80 to 200 minutes; Wherein, for every 0.015g of polyvinyl alcohol, the amount of photocatalyst used is 35-65mg; The photocatalyst is prepared by the following method: (1) adding the second liquid to the stirred first liquid to obtain a photocatalyst precursor; Wherein, the first liquid includes titanate and a first solvent; the first solvent includes a monohydric alcohol containing 1 to 6 carbon atoms and a carboxylic acid containing 1 to 6 carbon atoms; The second liquid includes a water-soluble inorganic lanthanum salt, polyvinyl alcohol and a second solvent; the second solvent includes water and a monohydric alcohol containing 1 to 6 carbon atoms; The molar volume ratio of the water-soluble inorganic lanthanum salt to the titanate is (0.0015-0.004):10 mol / L, and the mass volume ratio of the polyvinyl alcohol to the titanate is (0.1-0.2):10 g / L; (2) The photocatalyst precursor is calcined at 350-450° C. to obtain a photocatalyst.